Microstructural Response Of Powder Metallurgy (PM) RR1000 Superalloy To Inertia Friction Welding - Oluwasegun, K.M.; Adeoye, M.O.; Olorunniwo, O.E.; Atanda, P.O. (Ife Journal of Technology, 2011)
The microstructural response of powder metallurgy RR1000 superalloy to inertia friction welding was investigated. It was observed that the rapid heating during inertial friction welding resulted in a significant grain-boundary liquation of solid-state γ' precipitates, low temperature melting depressant intermetallic compound, and secondary solidification MC carbides constituents, which were all present in the preweld heat-treated alloy. Liquation of these particles enhanced grain boundary microfissuring in the thermomechanical affected zone (TMAZ) of the weldment. However, contrary to the generally observed increase in HAZ cracking in superalloys with an increase in Ti and Al concentration, due to increase in the hardness of the alloy and rapid re-precipitation of γ' strengthening particles during cooling from welding temperature, a significantly reduced cracking was observed in inertia friction welded PM RR1000 compared to the conventional gas tungsten arc welded cast IN738. This was despite the hardness being higher in the former than in the latter. This may be related to the solid state welding phenomena proffered by inertia friction welding which precludes the formation of liquid melt during welding.